Antiviral therapy and the development of osteopenia/osteoporosis among Asians with chronic hepatitis B. Issue 7 (27th February 2019) - Wei, Mike T.; Le, An K.; Chang, Matthew S.; Hsu, Holden; Nguyen, Pauline; Zhang, Jian Q.; Wong, Chris; Wong, Clifford; Cheung, Ramsey; Nguyen, Mindie H.
Abstract: Background: Recent studies have suggested a potential increase in the incidence of osteoporosis for patients receiving tenofovir disoproxil fumarate (TDF), but this issue remains controversial. Methods: The retrospective cohort study of 1224 Asian chronic hepatitis B (CHB) patients greater than 18 years without baseline osteopenia/osteoporosis seen at four US centers from 2008 to 2016. Patients were categorized into three groups—treatment‐naive patients who initiated therapy with TDF (1) or entecavir (ETV) (2), or untreated patients (3). Patients were followed until the development of osteopenia/osteoporosis or end of the study. Results: Of the 1224 study patients, 276 were treated with TDF, 335 with ETV, and 613 were untreated. The prevalence of cirrhosis was lower for untreated patients (2.6% vs 16.3% for TDF and 17.6% for ETV; P  < 0.001). The 8‐year cumulative incidence rate of osteopenia/osteoporosis was 13.17% for TDF, 15.09% for ETV, and 10.17% for untreated patients, with no statistically significant difference among the three groups ( P  = 0.218). On multivariate Cox regression controlling for demographics, osteoporosis risk factors, albumin, and hepatitis B virus (HBV) DNA levels, neither TDF (adjusted hazard ratio [HR] = 0.74; 95% confidence interval [CI]: 0.34 and 1.59) nor ETV (adjusted HR = 0.98; 95% CI: 0.51 and 1.90) were associated with increased osteopenia/osteoporosis risk compared with untreated patients. Conclusions: Our retrospective study suggests that there is no significant increase in the incidence of osteopenia/osteoporosis for patients with CHB treated with TDF or ETV during a median follow‐up of about 4 to 5 years. However, further study with longer follow‐up is needed as an anti‐HBV therapy, which is often lifelong or long‐term and the development of osteopenia/osteoporosis can be a slow process. Highlights: There is no significant increase in the incidence of osteopenia or osteoporosis for patients with chronic hepatitis B treated with tenofovir disoproxil fumarate or entecavir during a median follow‐up of about 4 to 5 years. Further study with longer follow‐up is needed as an anti‐HBV therapy, which is often lifelong or long‐term and the development of osteopenia and osteoporosis can be a slow process.